PENANAMAN NILAI-NILAI DASAR ISLAMI ANAK USIA DINI PADA MASYARAKAT PERKOTAAN - Isyatul Mardiyati (AT-TURATS, 2015)
Negative Social phenomena in urban society due to changes in lifestyle, social interaction, and changes in social systems have led to problems in many aspects of life. The social problems indicate that urban community is going through a phase of ‘demoralization’ as a result of social changes that are not in line with the Islamic basic values and other norms. The increasing cases of crime in urban areas in terms of quality and quantity, such as corruption, fraud, theft, assault, murder, etc. indicate that the quality of the character and behavior of individuals or groups are still low, resulting from insufficient religious education and norms they receive from an early age. In this light, the Kindergarten or Early Childhood Education plays a very important role in instilling basic Islamic values in children from an early age. The efforts can be made through a series of activities of ‘play and learn’ to actualize Islamic values in everyday life. These activities are expected to achieve a better generation in terms of mental and intellectual capacities, having noble character and strong faith as well as piety to Allah. In addition, through instillation of basic Islamic values from an early age, we will have a new generation of Muslims who act as agents of change that bring about the glory of Islam in the modern era.